Comprehensive approach to static firing tests of micro gas turbine engines powered by liquid fuels; Energy; Vol. 313 - Antonov D. V. Dmitry Vladimirovich; Cherkasov R. E. Roman Evgenjevich; Gneusheva V. V. Violetta Vitaljevna; Mikulich M. M. Mikhail Evgenjevich; Strizhak P. A. Pavel Alexandrovich; Yanovsky (Yanovskiy) Leonid Samoylovich L. S. (2024, 2024)
Title screen